2010
DOI: 10.1124/jpet.110.168070
|View full text |Cite
|
Sign up to set email alerts
|

A Claudin-Targeting Molecule as an Inhibitor of Tumor Metastasis

Abstract: Tumor metastasis of epithelium-derived tumors is the major cause of death from malignant tumors. Overexpression of claudin is observed frequently in malignant tumors. However, claudin-targeting antimetastasis therapy has never been investigated. We previously prepared a claudin-4-targeting antitumor molecule that consisted of the C-terminal fragment of Clostridium perfringens enterotoxin (C-CPE) fused to protein synthesis inhibitory factor (PSIF) derived from Pseudomonas exotoxin. In the present study, we inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 38 publications
0
21
1
Order By: Relevance
“…Here, particularly the claudin-specific binding property of the CPE C-terminal domain was employed to target other toxins, such as diphteria toxin fragment A (DT-A), Pseudomonas aeroginosa exotoxin (PE) or TNF-a. [39][40][41][42][43] These approaches exploit CPE-mediated targeting to introduce the toxic proteins into tumor cells, and were shown to be effective in vitro and in vivo. These strategies aimed rather at improvement of cytotoxicities of DT-A, PE or TNF-a, than the toxicity of CPE itself.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, particularly the claudin-specific binding property of the CPE C-terminal domain was employed to target other toxins, such as diphteria toxin fragment A (DT-A), Pseudomonas aeroginosa exotoxin (PE) or TNF-a. [39][40][41][42][43] These approaches exploit CPE-mediated targeting to introduce the toxic proteins into tumor cells, and were shown to be effective in vitro and in vivo. These strategies aimed rather at improvement of cytotoxicities of DT-A, PE or TNF-a, than the toxicity of CPE itself.…”
Section: Discussionmentioning
confidence: 99%
“…However, in vivo frequent applications of CPE and of CPE-fusion proteins were required to achieve therapeutic effects. [39][40][41]43 In contrast, CPE as a sole full-length protein combines both strong target specificity and very efficient cytotoxicity, which is important for in vivo applications to achieve rapid tumor destruction. This study demonstrated that although CPE is produced inside the transfected cells, its outside action for pore formation and cell lysis is not hampered.…”
Section: Discussionmentioning
confidence: 99%
“…What role these proteins serve in ovarian cancers is largely unknown, and data from studies addressing this question have yielded conflicting results (reviewed in Hewitt et al, 2006;Kominsky, 2006;Ouban and Ahmed, 2010). CLDN3 and CLDN4 are of particular interest in ovarian cancer therapy because CLDN3 and CLDN4 are the only transmembrane tissue-specific claudins capable of mediating Clostridium perfringens enterotoxin binding and cytolysis (Katahira et al, 1997); therefore, they have attracted attention as potential therapeutic targets (Morin, 2005;Kominsky, 2006;Kominsky et al, 2007;Yuan et al, 2009;Saeki et al, 2010). We made the novel observation that CLDN3 and CLDN4 modulate sensitivity to the cytotoxic effect of cDDP.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, c-cPE-PSIF did not lead to decreases of body weight and to any apparent biochemical side effects in treated mice. 26) Together, these findings indicate that CL-targeting therapy may be a potent antitumor strategy.…”
Section: Targeting Cancermentioning
confidence: 91%
“…We inoculated mice with 4T1 cells, a murine cell line frequently used as a spontaneous lung metastasis model, 26) then treated the mice with c-cPE-PSIF. c-cPE-PSIF significantly suppressed tumor growth ( Fig.…”
Section: Targeting Cancermentioning
confidence: 99%